The international legal mechanism for regulating grain trade in the context of the World Trade Organization (Journal of actual problems of jurisprudence, 2021)
This article considers the necessity and importance of the process of regulating grain trade at the international level, taking into account the effectiveness of the application of international treaties, the purpose of which is to resolve differences between countries and maintain a common grain policy. The article analyzes the chronology of legal problems of adaptation of the world grain industry and considers the issue of compliance of the current International Grains Agreement with the conditions of modern trade within the World Trade Organization. It should be noted that the provisions of the International Grains Agreement, taking into account the problems of hunger and food security, should comply with the principles of free trade, without hindering the development of the agricultural sector of the economy of developing countries. The article considers the legal aspects of the grain industry of the Republic of Kazakhstan in the conditions of its membership in the World Trade Organization. The analysis of compliance of the norms of the Kazakhstan legislation regulating the issues of regulation of the grain industry of the economy, the WTO regulatory and legal documentation is carried out. The study used the norms of the International Grains Agreement, the World Trade Organization, as well as official and scientific views in the field of legal problems of the formation, development and regulation of the grain sector. The purpose of the study is to identify the degree of effectiveness of international cooperation in the field of world grain trade, taking into account the issues of ensuring food security. At the same time, the authors propose to regulate the creation of a single global grain reserve through decisions taken by the International Grains Council.Keywords: grain trade, international trade law, World Trade Organization, grain trade disputes, international legal regulation.